Optimal signal control algorithm for signalized intersections under a V2I communication environment - Han, Eum; Lee, Hwan Pil; Park, Sangmin; So, Jaehyun; Yun, Ilsoo (Journal of Advanced Transportation, 2019)
This study aims to develop an optimal signal control algorithm for signalized intersections using individual vehicle's trajectory data under the vehicle-to-infrastructure (V2I) communication environment. The optimal signal control algorithm developed in this study consists of three modules, namely, a phase group length computation module, a split distribution module, and a phase sequence assignment module. A set of analyses using a microscopic simulation model, VISSIM, was conducted for evaluating the effectiveness of the V2I-based optimal signal control algorithm proposed in this study. The analysis results show that the performance of the V2I-based optimal signal control algorithm is superior to the actuated as well as the fixed signal control methods in an isolated intersection and a 2X3 signalized intersection network. In addition, this study investigated the minimum market penetration rate of V2I equipped vehicles for which the V2I-based optimal signal control algorithm is applicable.
Keywords: Communication environments; Distribution module; Fixed signal control; Isolated intersection; Microscopic simulation models; Optimal signal control; Signalized intersection; Vehicle to infrastructure (V2I)